The architectural representation of the past: Meaning versus emptiness on Pablo de Santis’ La sexta lámpara - Cavagnaro Farfán, Franco (2019)
What are the communicating vessels between architecture and literature, between the concrete and habitable, and what is the gap between the linguistic and the inhabitability of the space created through words? Our purpose is to show the complementarity and the differences between both disciplines, through the novel La Sexta Lámpara (2004) by Pablo De Santis, which centers its plot around the historical development of nineteenth century and modern architecture, the utopic projects of each and how they differ in the European and American geographic space. To establish these connections and develop them, the ideas of David Spurr in his book Architecture & Modern Literature (2012) are employed.